Magnitude of high body mass index and its associated factors among adult type 2 diabetes mellitus patients attending follow-up clinics at hospitals in Wolaita Zone, Southern Ethiopia, 2021 - Eshetu Elfios Endrias; Mulualem Gete Feleke (Elsevier, 2023)
Background: High body mass index in type 2 diabetes mellitus patients has been known to cause adverse impacts in treatment and prevention of diabetes-related complications. High body mass index has further been linked with poor control of blood pressure, cholesterol, and blood glucose levels among individuals with type 2 diabetes mellitus. So this study aimed to assess the magnitude of high body mass index and its associated factors among type 2 diabetes mellitus patients attending follow-up clinics at hospitals in Wolaita zone, Southern Ethiopia, 2021. Methods: Institution-based cross-sectional study was conducted from March 24 up to May 25, 2021. Sampled type 2 diabetes mellitus patients attending follow-up clinics at hospitals in the Wolaita zone were included. The sample size was determined using epi info version 7 and the final sample was 526. A systematic random sampling technique was used to select the study participants. Data were entered using epidata version 3.1 and analyzed using Statistical package software for social science version 25. Binary logistic regression was done to determine the relationship of each independent variable with the dependent variable. Both bivariable and multivariable analyses were conducted and those variables that showed a p-value less than 0.25 were the candidate for multivariable analysis. Then multivariable analysis by the step-wise backward method used and variables that showed p-value less than 0.05 with 95% CI were reported as statistically significant factors. Result: The magnitude of high body mass index was 49.9 %(CI: 45.4, 54). Female gender (AOR 1.978, CI (1.349, 2.901), alcohol drinking of 2-3 times per week (AOR: 2.442, CI (1.315, 4.432:), poor dietary practice (AOR: 1.964, CI (1.347, 2.864), being hypertensive (AOR: 1.543, CI (1.037, 2.296), and low physical activity (AOR: 3.108, CI (1.722, 5.609) were significantly associated with high body mass index. Conclusion and Recommendation: The magnitude of the high body mass index in this study was high. Being female, alcohol drinking 2-3 times per week, poor dietary practice, being hypertensive and low physical activity were significant factors associated with high body mass index in the study area. Health promotion and preventive programs such as dietary modification, alcohol restriction and physical exercise should be added to the therapeutic programs.